Impact of a community-based cardiovascular disease service intervention in a highly deprived area. Issue 5 (22nd August 2019) - Downing, Jennifer; Rose, Tanith C; Saini, Pooja; Matata, Bashir; McIntosh, Zoe; Comerford, Terence; Wilson, Keith; Pemberton, Allan; Harper, Lesley M; Shaw, Matthew; Daras, Konstantinos; Barr, Ben
Abstract : Objective: To examine the effects on emergency hospital admissions, length of stay and emergency re-admissions of providing a consultant-led, community-based cardiovascular diagnostic, treatment and rehabilitation service, based in a highly deprived area in the North West of England. Methods: A longitudinal matched controlled study using difference-in-differences analysis compared the change in outcomes in the intervention population, to the change in outcomes in a matched comparison population that had not received the intervention, 5 years before and after implementation. The outcomes were emergency hospitalisations, length of inpatient stay and re-admission rates for cardiovascular disease (CVD). Results: Findings show that the intervention was associated with 66 fewer emergency CVD admissions per 100 000 population per year (95% CI 22.13 to 108.98) in the post-intervention period, relative to the control group. No significant measurable effects on length of stay or emergency re-admission rates were observed. Conclusion: This consultant-led, community-based cardiovascular diagnostic, treatment and rehabilitation service was associated with a lower rate of emergency hospital admissions in a highly disadvantaged population. Similar approaches could be an effective component of strategies to reduce unplanned hospital admissions.